Literature and the World - Helgesson, Stefan (Literature and Contemporary Thought, 2020)
Literature and the World presents a broad and multifaceted introduction to world literature and globalization. The book provides a brief background and history of the field followed by a wide spectrum of exemplary readings and case studies from around the world. Amongst other aspects of World Literature, the authors look at: New approaches to digital humanities and world literature Ecologies of world literature Rethinking geography in a globalized world Translation Race and political economy Offering state of the art debates on world literature, this volume is a superb introduction to the field. Its critically thoughtful approach makes this the ideal guide for anyone approaching World Literature.